Time for bed, fred! ebook - Ismail, Yasmeen (2014)
Meet Fred-a mischievous, playful, loving dog. It's time for Fred to go to bed . . . but Fred really, really doesn't want to! From hiding up in trees, to splashing in muddy puddles, to hiding behind bookshelves, Fred will do anything to avoid bedtime. He would even rather have a bath than go to bed . . . but all of this running couldn't possibly have possibly made Fred sleepy-could it? Bound to strike a chord with parents and children with their own bedtime distraction techniques, Yasmeen Ismail's hilarious text and cheerful, vivid illustrations will have every reader shouting by the very last page, "Time for Bed, Fred!"